Pelatihan Pembuatan Media Ajar Multimedia Interaktif Berbasis IT di SMAN 1 V Koto Kp Dalam - Fudhla, Nora; Aulia, Fauzan; Oktoviandry, Rifki; Haq, Maulluddul (ABDI HUMANIORA: Jurnal Pengabdian Masyarakat Bidang Humaniora, 2023)
The community service described in this article aimed at offering solutions upon thelackof optimal empowerment of technological capabilities, and knowledge of creating teaching content for teachers at SMAN 1 V Koto Kp Dalam Padang Pariaman, in responding to the demands for ongoing digital learning. Based on the situation at school, these problems lead to two main problems, 1) the lack of teacher's ability to design digital teaching materials/teaching media and 2) the teacher's lack of understanding in choosing the right integrated digital learning application used to accommodate connections and collaboration between teachers and students. The solutions offered are providing a workshop that facilitates teacher to be able to create interactive teaching contents through digital multimedia application. Prior to the workshop, a need analysis was carried out to know the teachers’ perception on the use of digital multimedia application for learning process and what application would suit best to the teachers’ technological capability and situations. The results show teachers’ positive responds and needs of digital application to create teaching contents and a web-based application, namely Canva, was chosen to be taught. The teachers were then guided to produce teaching contents through several available features in Canva such as Presentation, Infographic, Worksheet and Video Making.